Online-Frachtenbörse für den transeuropäischen Schienengüterverkehr. - Bruns, Adina Silvia; Günes, Nazif; Zelewski, Stephan (Deutscher Verkehrs-Verl., 2010)
Der Zukunftstrend Green Logistics bietet erhebliches Marktpotenzial für den Schienengüterverkehr. Im EU-Verbundprojekt CODE24 werden vielfältige Initiativen ergriffen, um den Schienengüterverkehr entlang der Nord-Süd-Transversale Rotterdam/Genua nachhaltig zu stärken. Ein Teilprojekt befasst sich mit der Entwicklung und der Markteinführung einer Online-Frachtenbörse für die internetbasierte Abstimmung zwischen Nachfrage nach und Angebot von Gütertransporten im Schienengüterverkehr.

An essential part of implementing the future "Green Logistics" plan will be the acomplishment of moving freight transport from road to rail. It is noted that the share of reight traffic by rail, as part of the modal split system, has witnessed a very notable long term decrease that continues at present. It is against this background that the EU has launched the multi-national joint research project CODE24 in order to render freight transport by rail more attractive, on a long term basis, along Europe's north-south transversal route linking Rotterdam and Genoa. Viewed from the aspect of economic management, the development of an online auction-based freight exchange for trans-European freight transport by rail is the focal point for the project-related work ahead. Also highlighted are the inherent opportunities and risks, which may have to be faced connection with such an online freight exchange, notably so in regard to the wished-for intensification of trans-European freight transport by rail.
Trans-European freight transport with the help of an online freight exchange.
Keywords: Verkehr; Güterverkehr; Schienengüterverkehr; Güterfernverkehr; Kapazitätsplanung; Forschungsprojekt; Grenzüberschreitender Verkehr; Logistik; Nachhaltigkeit; Frachtverkehr; Internet; Tourenplanung; Transportleistung